Efektifitas Model Discovery Learning Berbantuan Gnomio dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pelajaran Ekonomi (Business and Accounting Education Journal, 2022)
The purpose of this study was to determine the effectiveness of the Gnomio-assisted discovery learning model on students' critical thinking skills in Economics class XI IPS subject on Taxes at SMAN 2 Temanggung. The population in this study were students of class XI IPS SMAN 2 Temanggung. The sample in this study used purposive sampling, in accordance with the purposive requirements of class XI IPS 4 as the experimental class. Data collection techniques used include tests and observations. Data analysis used paired T-test. The results showed that the Gnomio-assisted discovery learning model was able to increase the KKM score, increase the proportion of completeness by 75% and have a significant effect on critical thinking skills. The conclusion of this study is that the discovery learning model assisted by gnomio is able to increase the KKM score and improve the critical thinking skills of class XI IPS students in economics lessons on taxation material even though the increase is low. The advice given is that the teacher is expected to make habituation to students using the Gnomio-assisted discovery learning model so that this model can be applied optimally.